Tantalum–Zirconium Co‐Doped Metal–Organic Frameworks Sequentially Sensitize Radio–Radiodynamic–Immunotherapy for Metastatic Osteosarcoma. Issue 10 (5th February 2023) - Li, Tao; Gao, Mingquan; Wu, Zifei; Yang, Junjun; Mo, Banghui; Yu, Songtao; Gong, Xiaoyuan; Liu, Jing; Wang, Weidong; Luo, Shenglin; Li, Rong
Abstract: Due to radiation resistance and the immunosuppressive microenvironment of metastatic osteosarcoma, novel radiosensitizers that can sensitize radiotherapy (RT) and antitumor immunity synchronously urgently needed. Here, the authors developed a nanoscale metal–organic framework (MOF, named TZM) by co‐doping high‐atomic elements Ta and Zr as metal nodes and porphyrinic molecules (tetrakis(4‐carboxyphenyl)porphyrin (TCPP)) as a photosensitizing ligand. Given the 3D arrays of ultra‐small heavy metals, porous TZM serves as an efficient attenuator absorbing X‐ray energy and sensitizing hydroxyl radical generation for RT. Ta–Zr co‐doping narrowed the highest occupied molecular orbital‐lowest unoccupied molecular orbital (HOMO–LUMO) energy gap and exhibited close energy levels between the singlet and triplet photoexcited states, facilitating TZM transfer energy to the photosensitizer TCPP to sensitize singlet oxygen ( 1 O2 ) generation for radiodynamic therapy (RDT). The sensitized RT–RDT effects of TZM elicit a robust antitumor immune response by inducing immunogenic cell death, promoting dendritic cell maturation, and upregulating programmed cell death protein 1 (PD‐L1) expression via the cGAS–STING pathway. Furthermore, a combination of TZM, X‐ray, and anti‐PD‐L1 treatments amplify antitumor immunotherapy and efficiently arrest osteosarcoma growth and metastasis. These results indicate that TZM is a promising radiosensitizer for the synergistic RT and immunotherapy of metastatic osteosarcoma. Abstract : Ta–Zr co‐doped nanoscale metal−organic framework (nMOF) as a versatile radiosensitizer can offer significantly enhanced RT and RDT effects to elicit a robust antitumor immune response by activating the cGAS–STING pathway. Given its favorable properties of near‐infrared fluorescent/CT/PA multimodal imaging and good biocompatibility, this novel nMOF‐based radiosensitizer has potential applications in the efficient and precise treatment of osteosarcoma.